Managing Service-Specific and Open-Posting Block Sizes when Allocating Operating Room Time. Issue 1 (2nd January 2018) - Taaffe, Kevin; Fredendall, Lawrence; Weiss, Rebecca
ABSTRACT: The perioperative services (periop) manager establishes policies to manage the operating room (OR) resources that affect both patient and surgeon satisfaction with the hospital's service. Both the surgeon and the patient are customers of the periop department, and their satisfaction is a measure of the service quality. The periop manager uses block scheduling to allocate OR time. This technique gives one surgical practice (or service specialty) priority access to a block of time for scheduling procedures in an OR. Hospitals seek to obtain more of the surgeon's practice by allocating blocks to the surgeon, but the hospital must balance this OR time allocation with the risk that the OR time may not be used. In doing so, the periop manager creates a schedule that balances the hospital's risk of staff working overtime (beyond the OR's scheduled hours of blocked time) with the risk of staff being idle during a block of time reserved for a surgical practice that did not use it. The authors propose an OR management policy that creates service-specific blocks of OR time as well as open-posting blocks (those blocks shared by all surgical practices) and propose that this policy can increase access to the OR for more surgeons and, consequently, increase both surgeon and patient satisfaction. Through the use of two quality metrics–averseness to overtime and flexibility in sharing block time across services–this article examines how the setting of these two metrics affects OR performance. Historical data were used as an input into a modeling framework that created a feasible block schedule for a set of ORs. The block allocation schedule was then evaluated, with a portion of the data set reserved for testing. In an experiment at a large teaching hospital, results indicated that for every 20 percent increase in a manager's averseness to overtime, the hours in reserved blocks increased by 3 percent and utilization decreased by 2 percent. Similarly, a 33 percent increase in open posting flexibility translated into a reduced need of one OR.